Influence of plant and soil layer on energy balance and thermal performance of green roof system. (15th December 2017) - He, Yang; Yu, Hang; Ozaki, Akihito; Dong, Nannan; Zheng, Shiling
Abstract: This paper aims to make clear the effects of two important parameters, namely thickness of soil layer and leaf area index of plant layer, on green roof energy and thermal performance. Based on a coupled hygrothermal transfer model validated by field experiments in Shanghai area, energy balance of plant and soil layer is analyzed. Then 18 cases are simulated for different combinations of soil thickness and leaf area index, the results show that soil thickness has a significant effect on long term thermal performance of green roof in both summer and winter, while the effect of leaf area index is only great in summer. Compared with the hypothetical case without evaporation and transpiration, it is found that evaporation of soil layer makes a greater contribution in summer but a less one in winter compared with insulation effect of soil layer. For plant layer, shading is the main cooling way of roof deck while transpiration plays a minor role. Finally, based on the simulation results of long-term thermal performance, two new indexes are proposed to evaluate the relative thermal characteristic of green roof. And the influences of soil thickness, leaf area index and evapotranspiration on the two indexes are analyzed respectively. Highlights: Energy balance analysis of plant and soil layer are conducted in summer and winter. Effect of soil thickness and LAI on green roof thermal performance are presented. The influence of insulation and evaporation effect of soil layer are analyzed. The influence of transpiration and shading effect of plant layer are analyzed. Green roof performance is evaluated by two new indexes based on internal mechanism.